Vaksinasi Meningitis pada Jamaah Umroh di Kantor Kesehatan Pelabuhan Ambon - Elpira Asmin; Astina Astina (Universitas Majalengka, 2023)
The number of pilgrims at the time of the Umrah pilgrimage is very large from various countries, so there is a risk of spreading meningitis. So that a government regulation regarding meningitis vaccination is enforced for Hajj pilgrims who want to go for Hajj in Saudi Arabia. The purpose of this activity is to prevent the pilgrims from getting meningitis. The methods used are health screening, vaccination injection, data validation by KKP. The results of this examination are pilgrims whose istithaah status is declared sick but are allowed to go for Umrah. However, assistance is needed such as drug assistance so that the health of Hajj/Umrah pilgrims is guaranteed by Law No. 8 of 2019 concerning the implementation of Hajj and Umrah.